How did the iron industry from the Iron Age to the Roman Period in Southern Britain? - Crabb, S (2018)
This thesis explores the transition between the Iron Age and Roman periods in Britain using one of the most survivable and data packed archaeological artefacts, iron smelting slag. By using a series of complimentary analytical methods it is possible to reconstruct the smelting process. Not just on a purely metallurgical level but also revealing some of the actions of the smelters. The transition from the Iron Age to the Roman period has been a longstanding area of discussion in European archaeology, marking the change from prehistory to protohistory. A geographical limitation has been placed on this study to southern Britain, this is to cover the area with the most complete coverage of archaeological sites and also with a distinct archaeological change between the two periods. The analysis of smelting slag at a macromorphological level reveals furnace morphology and operation. The microstructure of the slag examined using reflective light microscopy reveals under what conditions the slag solidified. The chemical composition of slag determined using Scanning Electron Microscopy Energy Dispersive Spectroscopy (SEM-EDS) reveals the inputs to the smelting process and through their interaction the temperature and chemical change within the furnace. Combining these methods adds further information about the smelt, giving the reasons for the identifiable characteristics of the smelt. Traditional metallurgical analysis of iron smelting slag has focussed on the purely technical result of the smelt, effectively how efficient the smelt was and what ore was being used. The results of this study indicate that the production of iron from the earliest period in Britain was part of a complicated wider picture of resource exploitation, interaction between groups geographically and temporarily.